Structurally defined tandem-responsive nanoassemblies composed of dipeptide-based photosensitive derivatives and hypoxia-activated camptothecin prodrugs against primary and metastatic breast tumors - Mengchi Sun; Hailun Jiang; Tian Liu; Xiao Tan; Qikun Jiang; Bingjun Sun; Yulong Zheng; Gang Wang; Yang Wang; Maosheng Cheng; Zhonggui He; Jin Sun (Elsevier, 2022)
Substantial progress in the use of chemo-photodynamic nano-drug delivery systems (nano-DDS) for the treatment of the malignant breast cancer has been achieved. The inability to customize precise nanostructures, however, has limited the therapeutic efficacy of the prepared nano-DDS to date. Here, we report a structurally defined tandem-responsive chemo-photosensitive co-nanoassembly to eliminate primary breast tumor and prevent lung metastasis. This both-in-one co-nanoassembly is prepared by assembling a biocompatible photosensitive derivative (pheophorbide-diphenylalanine peptide, PPA-DA) with a hypoxia-activated camptothecin (CPT) prodrug [(4-nitrophenyl) formate camptothecin, N-CPT]. According to computational simulations, the co-assembly nanostructure is not the classical core-shell type, but consists of many small microphase regions. Upon exposure to a 660 nm laser, PPA-DA induce high levels of ROS production to effectively achieve the apoptosis of normoxic cancer cells. Subsequently, the hypoxia-activated N-CPT and CPT spatially penetrate deep into the hypoxic region of the tumor and suppress hypoxia-induced tumor metastasis. Benefiting from the rational design of the chemo-photodynamic both-in-one nano-DDS, these nanomedicines exhibit a promising potential in the inhibition of difficult-to-treat breast tumor metastasis in patients with breast cancer.